Students’ Speaking Development Through Word Adventure Game-Based Learning - Salsabila Umi Nur Fajria; Dwi Fita Heriyawati (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Game-based language learning has increasingly been adopted in English as a Foreign Language classrooms to support speaking practice through interactive digital environments. Specific Background One such approach is the use of Word Adventure, a gamified learning tool designed to simulate real-life communication scenarios for junior high school learners. Knowledge Gap Previous studies on game-based language learning have largely emphasized learning outcomes, while limited attention has been given to learners’ own perspectives, particularly in contexts with constrained internet access. Aims This study aimed to explore how Word Adventure supports the development of students’ speaking skills and to examine students’ perceptions and experiences when using the game in EFL instruction. Results Using a qualitative descriptive design, data from semi-structured interviews with four seventh-grade students revealed increased motivation, confidence, fluency, and contextual language use, alongside heightened enjoyment and collaborative learning, although technical and conceptual challenges were reported. Novelty This study provides learner-centered qualitative evidence on an online–offline accessible game-based tool by foregrounding students’ lived experiences in speaking practice. Implications The findings suggest that Word Adventure can serve as a practical alternative for fostering speaking development and learner engagement in junior high EFL contexts with limited technological infrastructure. Highlights: Learners reported stronger engagement and willingness to participate in oral practice. Repetitive interactive tasks supported smoother and faster oral production. Narrative-driven activities encouraged cooperation and meaningful classroom interaction. Keywords: Game-Based Language Learning, Speaking Skills, Student Perceptions, EFL Classroom